THE INFLUENCE OF ENTREPRENEURSHIP LEARNING ON ENTREPRENEURIAL INTEREST OF CLASS XII STUDENTS IN PUBLIC SCHOOL 6 MAKASSAR - Muchtar, Nur Fadilah; Sangkala, Masnawaty; Rijal, Abdul; Dunakhir, Samirah; Azis, Muhammad (Universitas Labuhanbatu, 2024)
This study aims to determine the influence of entrepreneurship learning on entrepreneurial interest in class XII students at SMK Negeri 6 Makassar. The variables in this study are entrepreneurship learning as the independent variable and interest in entrepreneurship as the dependent variable. The population and this research are all class XII students at SMK Negeri 6 Makassar. The sampling technique used the Random Sampling technique, samples from the population were obtained and a portion of the population with a sample of 76 students. The data collection technique used was a questionnaire and technical documentation. The data analysis used was descriptive analysis of percentages, instrument reliability testing and hypothesis testing. Based on the results of the data analysis that has been done, the results of the descriptive analysis of entrepreneurship learning are 85.52 percent which are very high and the interest in entrepreneurship is 80.26 percent which is high. And the results of simple linear regression analysis are obtained entrepreneurship learning Y-27470-1.228X, which means that each addition of 1 value learning then the interest in entrepreneurship has increased 1.228 While the product moment correlation test obtained a correlation coefficient value of 0.555 and is in the medium category which means the effect of entrepreneurship learning on moderate entrepreneurship interest. The results of the analysis of the coefficient of determination (r) obtained (r) = 0.308 or 30.8%, which means that learning entrepreneurship has a contribution to interest in entrepreneurship by 30.8 percent and the remaining 69.2 percent is influenced by other factors. While the results of the t- test analysis obtained a significant value of 0.000 0.05, which means that entrepreneurship learning has a significant effect on interest in entrepreneurship, thus the hypothesis is acceptedKeywords: Entrepreneurship Learning, Interest in Entrepreneurship